Wakefield excitation in dielectric waveguides by a sequence of relativistic electron bunches - Kiselev, V.A.; Onishchenko, I.N.; Sotnikov, G.V. (Вопросы атомной науки и техники, 2015)
The results of theoretical and experimental studies of the wakefield excitation in a dielectric waveguide of а fi-nite length by a long sequence of relativistic electron bunches was carried out to reveal the possibility of the wakefield amplitude enhancement at summing coherent fields of separate bunches when the bunch repetition frequency coincides with the excited field frequency. In accordance with the theory the stepwise increasing dependence of the wakefield amplitude upon the dielectric waveguide length was experimentally obtained. Проведено теоретичні та експериментальні дослідження збудження кільватерного поля в діелектричному хвилеводі кінцевої довжини довгою послідовністю релятивістських електронних згустків для з'ясування можливості збільшення амплітуди кільватерного поля підсумовуванням полів окремих згустків при збігу частоти повторення згустків з частотою збуджуваного поля. Згідно з теорією отримано експериментально ступеневе збільшення амплітуди кільватерного поля залежно від довжини діелектричного хвилеводу. Проведены теоретические и экспериментальные исследования возбуждения кильватерного поля в диэлектрическом волноводе конечной длины длинной последовательностью релятивистских электронных сгустков для выяснения возможности увеличения амплитуды кильватерного поля суммированием полей отдельных сгустков при совпадении частоты повторения сгустков с частотой возбуждаемого поля. Согласно теории получено экспериментально ступенчатое увеличение амплитуды кильватерного поля в зависимости от длины диэлектрического волновода.